Digitalization of Ancient Manuscripts from Tuban Regency as Historical Sources - Supriyanto Supriyanto (UIN Imam Bonjol Padang, 2024)
Manuscripts are the result of a person's handwriting, which contains various information, including thoughts, community culture, life history, customs in the past, which become a source of historical studies, and so on. Manuscripts in Indonesia are widely scattered throughout the country, including manuscripts in Tuban Regency. Tuban has a solid Islamic history. This is evidenced by the existence of handwritten evidence that contains various ancient manuscript information. Many people need to learn more information about the existence of manuscripts. Until care and preservation are often ignored. This method uses a philological approach focusing on a series of ancient manuscript text studies. Starting at the inventory stage of field study data collection, conservation preservation, digitization, and digital data processing. The manuscript study focuses on the Tuban Regency area by visiting several active institutions such as museums, Islamic boarding schools, and some residents. This study requires a spatial topography to ensure the condition of the manuscripts is realized based on geographical conditions and adjusts to the temperature and light entities. It can be found that some manuscripts need to be revised due to inadequate care. Manuscript preservation efforts have been carried out through various challenges, such as looking at biological, physical, and chemical factors and factors due to human negligence. Involves the challenge of providing the digital world with a place to store information on various kinds of manuscripts.